RF-MEMS based oscillators - Nordin, Anis Nurashikin (IGI-Global, 2012)
Today’s high-tech consumer market demand complex, portable personal wireless consumer devices which are low-cost and have small sizes. Creative methods of combining mature integrated circuit (IC) fabrication techniques with innovative radio-frequency micro-electro-mechanical systems (RF-MEMS) devices has given birth to wireless transceiver components which are operated at higher frequencies but manufactured at the low-cost of standard ICs. Oscillators, RF bandpass filters and low noise amplifiers are the most critical and important modules of any wireless transceiver. Their individual characteristics determine the overall performance of a transceiver. This chapter illustrates the RF oscillators which utilize MEMS devices as their frequency generator. Emphasis will be given to the design of oscillators to suit the modern wireless communication systems. Several different types of oscillators are discussed namely ring, LC and voltage-controlled-oscillator. Reviews of current RF-MEMS oscillator circuits will also be given.